HAPUSNYA LEMBAGA PARATE EKSEKUSISEBAGAI AKIBAT HUKUM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 - Budi, Antonius (UI Scholars Hub, 2021)
A security rights holder has 2 methods of carrying out executions without resorting to a lawsuit so that they can carry out executions quickly and easily: parate executie or executorial titles. In the Constitutional Court Ruling Number 18/PUU-XVII/2019, parate executie is considered as a continuation of theexecutorial titles. This causes the abolition of parate executie in fiduciary agreement, because now creditor who wishes to exercise parate executie must do so withthe consensus of the debtor or through legal methods. This is contrary to the legal theoryand function of parate executie which is summary execution outside the court system under creditors own right. Furthermore, by comparing it with the Supreme Court Ruling Number 3210K/Pdt/1984, the authors examine whether the abolition of parate executie in fiduciary will also hinder the execution of parate executie on other security rights other than fiduciary. The writer ends with a suggestion for the writer of theAcademic Draft of the Fiduciary Bill to continue to strengthen the existence of a parate executie on fiduciary guarantees as a follow-up to the Constitutional Court Ruling Number 18/PUU-XVII/2019.